2016
DOI: 10.1097/jom.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Postoffer Pre-Placement Screening for Carpal Tunnel Syndrome in Newly Hired Manufacturing Workers

Abstract: Objective We determined the predictive validity of a post-offer pre-placement (POPP) screen using nerve conduction velocity studies (NCV) to identify future cases of carpal tunnel syndrome (CTS). Methods A cohort of 1648 newly hired manufacturing production workers underwent baseline NCS, and were followed for 5 years. Results There was no association between abnormal POPP NCV results and incident CTS. Varying NCV diagnostic cut-offs did not improve predictive validity. Workers in jobs with high hand/wrist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, some investigators have shown that testing for EDX post‐offer but pre‐employment is not a worthwhile endeavor. Dale et al ., in a large retrospective cohort study of 1,648 newly hired manufacturing production workers, showed no association between abnormal pre‐placement EDX results and incident CTS; they concluded that EDX screening is ineffective as a preventive strategy for CTS.…”
mentioning
confidence: 97%
“…In addition, some investigators have shown that testing for EDX post‐offer but pre‐employment is not a worthwhile endeavor. Dale et al ., in a large retrospective cohort study of 1,648 newly hired manufacturing production workers, showed no association between abnormal pre‐placement EDX results and incident CTS; they concluded that EDX screening is ineffective as a preventive strategy for CTS.…”
mentioning
confidence: 97%